Fracture of the penis with urethral rupture - Roy, MK; Matin, MA; Alam, MM; Suruzzaman, M; Rahman, MM (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):70-3. The abstract of this article is available on the PubMed website